2018
DOI: 10.2147/prbm.s173692
|View full text |Cite
|
Sign up to set email alerts
|

One health behaviour or many health-related behaviors?

Abstract: ObjectiveOf the many existing health models, models of health behavior are considered optimal for research and application as they focus on concrete forms of behavior that support, maintain, or undermine one’s health, and they accentuate the individual as the initiator of this behavior. Research in this area follows a broad range of concrete partial manifestations of health behavior. Is it necessary to differentiate between various types of health behavior or could these partial manifestations be combined unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Therefore, when planning policies and designing and evaluating interventions, the behavior patterns within these clusters should be considered [20,49,51]. However, previous studies have not consistently identified the occurrence of these clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when planning policies and designing and evaluating interventions, the behavior patterns within these clusters should be considered [20,49,51]. However, previous studies have not consistently identified the occurrence of these clusters.…”
Section: Discussionmentioning
confidence: 99%
“…There are two directions of behaviour, i.e. favourable (healthy behaviour) or threatening to health (unhealthy, self-destructive behaviour) [ 1 ]. Caring for physical health consists in maintaining personal hygiene and one’s own environment, undertaking appropriate physical activity as well as rational nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of oral health is an essential requirement for health-related behavior, and awareness increases with age. Health-related behaviors are defined as the activities carried out by individuals to protect, encourage, or preserve health and to prevent disease [ 2 ]. Oral care products are those with the purpose of mouth cleansing, breath freshening, and maintaining oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Other oral hygiene aids are also used by individuals, either on the recommendation of a dentist or voluntarily. Factors such as education, wages, advertisements, and personal choices involving taste/flavor, color, and presentation of the product, among others, play roles in the choice of an oral hygiene product [ 2 ]. The maintenance of adequate oral health depends on the adoption of specific behaviors, including regular dental check-ups [ 4 ], brushing frequency [ 5 ], diet and sugar consumption [ 6 ], dental floss use, and other methods of interproximal cleaning [ 7 ].…”
Section: Introductionmentioning
confidence: 99%